Emergency general surgery: impact of distance and rurality on mortality. Issue 2 (25th April 2022) - Wohlgemut, Jared M.; Ramsay, George; Bekheit, Mohamed; Scott, Neil W.; Watson, Angus J. M.; Jansen, Jan O.
Abstract: Background: There is debate about whether the distance from hospital, or rurality, impacts outcomes in patients admitted under emergency general surgery (EGS). The aim of this study was to determine whether distance from hospital, or rurality, affects the mortality of emergency surgical patients admitted in Scotland. Methods: This was a retrospective population-level cohort study, including all EGS patients in Scotland aged 16 years or older admitted between 1998 and 2018. A multiple logistic regression model was created with inpatient mortality as the dependent variable, and distance from hospital (in quartiles) as the independent variable of interest, adjusting for age, sex, co-morbidity, deprivation, admission origin, diagnosis category, operative category, and year of admission. A second multiple logistic regression model was created with a six-fold Scottish Urban Rural Classification (SURC) as the independent variable of interest. Subgroup analyses evaluated patients who required operations, emergency laparotomy, and inter-hospital transfer. Results: Data included 1 572 196 EGS admissions. Those living in the farthest distance quartile from hospital had lower odds of mortality than those in the closest quartile (OR 0.829, 95 per cent c.i. 0.798 to 0.861). Patients from the most rural areas (SURC 6) had higher odds of survival than those from the most urban (SURC 1) areas (OR 0.800, 95 per cent c.i. 0.755 to 0.848). Subgroup analysis showed that these effects were not observed for patients who required emergency laparotomy or transfer. Conclusion: EGS patients who live some distance from a hospital, or in rural areas, have lower odds of mortality, after adjusting for multiple covariates. Rural and distant patients undergoing emergency laparotomy have no survival advantage, and transferred patients have higher mortality. Abstract : The aim of this study was to determine whether distance from hospital, or rurality, affects the mortality of Scottish emergency general surgery (EGS) patients. The study found that EGS patients who live some distance from a hospital, or in rural areas, have lower odds of mortality, after adjusting for multiple covariates. Rural and distant patients undergoing emergency laparotomy have no survival advantage, and transferred patients have higher mortality.